2021
DOI: 10.1177/2042098621989134
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events associated with sodium glucose co-transporter 2 inhibitors: an overview of quantitative systematic reviews

Abstract: Background: Multiple published quantitative systematic reviews have reported on adverse events associated with the use of sodium glucose co-transporter 2 (SGLT-2) inhibitors in patients with type 2 diabetes mellitus. Aims: To summarize and appraise the quality of evidence from quantitative systematic reviews assessing adverse events of SGLT-2 inhibitors. Methods: We searched PubMed, EMBASE and the Cochrane Library for quantitative systematic reviews assessing SGLT-2 inhibitor safety. Two reviewers extracted da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 65 publications
1
46
1
1
Order By: Relevance
“…Taken together, the rationale for co‐administration of pioglitazone and canagliflozin (or other SGLT‐2 inhibitors in general), particularly in the early stage of T2DM similar to the subjects in this study, is scientifically sound with respect to the pathophysiological background of T2DM such as increased insulin resistance/decreased beta‐cell function and a broad range of metabolic abnormalities including lipids. Both these drugs are known to possess CV protection, though certain adverse events could be a concern as described in Introduction 1‐7 . Nevertheless, if CV risks are reduced with these drugs, this might outweigh the risk of such adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the rationale for co‐administration of pioglitazone and canagliflozin (or other SGLT‐2 inhibitors in general), particularly in the early stage of T2DM similar to the subjects in this study, is scientifically sound with respect to the pathophysiological background of T2DM such as increased insulin resistance/decreased beta‐cell function and a broad range of metabolic abnormalities including lipids. Both these drugs are known to possess CV protection, though certain adverse events could be a concern as described in Introduction 1‐7 . Nevertheless, if CV risks are reduced with these drugs, this might outweigh the risk of such adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Other meta-analyses have not found other SGLT-2 inhibitors to be associated with an increased risk of either fracture or AKI. 73 Last, none of the included trials reported any amputation events. Further research is needed to rule out an association and/or quantify a more precise association between ipragliflozin and these adverse events.…”
Section: Resultsmentioning
confidence: 99%
“…Their results may guide decision‐making by healthcare providers, researchers and funding agencies, and inform patients and caregivers 11 . Previous overviews of SRs have focused on cancer risks and adverse events regarding the use of SGLT2 inhibitors 9,10 . The present overview summarizes the SRs' information about both the efficacy and safety of the SGLT2 inhibitor class in the treatment of T2DM.…”
Section: Discussionmentioning
confidence: 99%